The Effect of Earthquake Disaster Management Preparedness Knowledge and Training on Midwife Preparedness in Central Aceh Regency, Indonesia - Hasritawati; Sri Wahyuni MS; Barirah Madeni (Community Medicine and Education Journal, 2023)
The threat of an earthquake has received wide attention, because it is sudden, predictable, but difficult to determine when it will occur. Predictions are based on the monitoring of seismic activity, historical records and observations. Disasters always have an adverse impact, such as damage to physical facilities and infrastructure (residential housing, office buildings, schools, places of worship, roads, bridges and others). Midwives are health workers who generally work in Health Center or in the community/community closest to the impact of the disaster. The contribution of the midwife to disaster/emergency risk reduction or preparedness is very important. Meanwhile, midwives are often not included in the workforce for disaster preparedness at local, national and international levels. This study aimed to determine the effect of knowledge and training on earthquake disaster preparedness on the preparedness of midwives in Central Aceh Regency. This study uses a survey research design that is analytic in nature with an approach cross-sectional which is measured at the same time as the research takes place and tested through hypothesis testing. The sample is 208 samples. The sampling method in this study was carried out proportionally in proportion to the total population spread across 14 Districts in Central Aceh Regency. The results of the study show that there is an influence of knowledge variables (p = 0.018), and disaster training (p = 0.000). This shows that knowledge and training have a relationship and influence on earthquake disaster preparedness in Central Aceh Regency.